EFFECT OF BODY MASS INDEX ON LEFT VENTRICULAR MASS - Estephan, May Fadheel (Al-Nahrain Journal of Science, 2010)
Increased left ventricular mass (LVM) as determined by 2-dimensioned M-modeechocardiography is a predictor of cardiovascular morbidity and mortality.Objective: The aim of this study was to investigate the relationship between LVM and body massindex (BMI) categories in cross section study.Methods: LVM were measured by using M-mode echocardiography in a sample of 160 individuals(male 71, female 89) with age ranging from 16-80 years, referred by a physician. Those with apositive history of hypertension (HT), diabetes mellitus (DM), coronary artery disease (CAD)constituted 82 individuals; the remaining 78 were regarded as a control group negative for cardiacapparent problems.Results: Mean interior ventricular septum diastolic (IVSd), left ventricular posterior wall diastolic(LVPWd) and LVM were increased in cases group (the subjects with one or more of the followingillness ((HT), (DM), and (CAD)) compared to normal control.The mean IVSd, LVPWd showed a statistical of significant weak positive linear correlationwith BMI while the mean of the left ventricular interior dimension diastolic (LVIDd) and LVM wassignificantly higher among obese subjects compared to the subjects with normal BMI among thetotal sample. Among the subgroup of controls, only the LVM retained its positive linear correlationwith BMI.Conclusions: LVM was positively associated with BMI and this association seems to beindependent of other cardiac diseases associated with BMI.The remaining three parameters showed a weak association after adjusting for age, gender, and presence problems